Polymorphisms of interferon‐λ4 and IL28B – effects on treatment response to interferon/ribavirin in patients with chronic hepatitis C. Issue 1 (10th November 2013) - Stättermayer, A. F.; Strassl, R.; Maieron, A.; Rutter, K.; Stauber, R.; Strasser, M.; Beinhardt, S.; Datz, C.; Scherzer, T.‐M.; Steindl‐Munda, P.; Gschwantler, M.; Trauner, M.; et al.
Summary Background The IL28B genotype in rs12979860 predicts success of peginterferon/ribavirin (PEG/RBV) therapy in patients with chronic hepatitis C (CHC). Recently, a dinucleotide frame shift variant in ss469415590 (TT or ΔG) was described, which generates the novel interferon lambda 4 protein (IFNL4). IFNL4 ss469415590 (ΔG) allele carriers have an impaired clearance of HCV infection and response to IFN‐α therapy. In this study, we compared the role of IFNL4 polymorphism with the two commonly used IL28B SNPs rs12979860 and rs8099917 on response to PEG/RBV in patients with CHC. Aim To compare the role of IFNL4 polymorphism with the two commonly used IL28B SNPs rs12979860 and rs8099917 on response to PEG/RBV in patients with CHC. Methods A total of 754 PEG/RBV patients treated (male/female = 484/270; Caucasians: 98.8%; mean age: 42.8 [CI 95%: 42.0–43.6] y; genotype (GT)1: n = 435, GT2: n = 23, GT3: n = 185, GT4: n = 114) were investigated. Liver fibrosis was assessed by liver biopsy in 456 patients. Single nucleotide polymorphisms (SNPs) in ss469415590, rs12979860 and rs8099917 were analysed by RT‐PCR system. Results Of the patients, 12.9% (n = 97) had the ss469415590 ΔG/ΔG genotype (IFNL4), 51.3% (n = 387) were heterozygous (TT/ΔG) and 35.8% (n = 270) had TT/TT. IFNL4 polymorphism was independently associated with SVR in GT1 (OR: 2.539, CI 95%: 1.629–3.021, P < 0.001) and GT4 (OR: 12.573, CI 95%: 3.427–46.133, P < 0.001), but not in GT3 (OR: 1.514, CI 95%: 0.933–2.458, P = 0.093). IFNL4 correlated strongly with rs12979860 (ρ = 0.988, P < 0.001), but only moderately with rs8099917 (ρ = 0.598, P < 0.001). Conclusions These findings underscore the role of IFNL4 for treatment response in patients with CHC genotypes 1 and 4. However, due to its strong correlation with rs12979860 in IL28B, there is no benefit in additional testing for IFNL4 for treatment prediction in Caucasian patients. By contrast, IFNL4 improves prediction of response to interferon‐based therapies, if SNP rs8099917 is used.